Vacuum System Assisted Fdm – Characteristic Of Heat Transfer Using Finite Element Analysis - Maidin, Shajahan; John Wong, Huang Ung; Akmal, Suriati; Romlee, Wan Fatin Athirah; Mohamed, Ahmad Syafiq (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
Fused deposition modeling (FDM) process is one of the most efficient and used additive manufacturing technologies. For years, building functional components with good mechanical strength has been a difficult task. Generally, FDM process is operated in a room with or without an enclosure to produce physical polymer components. Therefore, the inconsistencies from different environmental factor such as temperature and air quality have indirectly affected its quality build. Vacuum technology has been used in the wide area of applications by creating an empty space of matter. However, there is no investigation of FDM operated in a vacuum environment. This paper aims to study the behaviour of the temperature inside a vacuum assisted FDM by performing finite element analysis. A heated nozzle and heated bed will be placed inside a vacuum chamber with a constant heat source and the initial temperature set at room temperature. The pressure range from 30 inHg (1 atm) to 1 inHg will be the manipulated variable. The result shows that as the pressure decreases, the transient heat transfer (natural convective heating) also reduced and the velocity of air flow became more consistent. This study was able to prove how different vacuum pressures can affect the heat inside a vacuum chamber. Results from this study can be used to further analyse the mechanical strength of vacuumed printed components in actual experimentations